Classification and treatment of food impaction - Ma, Wenxi; Zhou, Jianye; Ma, Bin (Frontiers in Dental Medicine, 2025)
Food impaction is a prevalent dental issue where food becomes trapped in interproximal spaces or near restored teeth, leading to discomfort, periodontal disorders, and tooth wear. This review explores the classification and treatment of food impaction, focusing on vertical and horizontal types. Effective management necessitates a thorough examination of the underlying causes to determine the most suitable approach. Vertical impaction is typically addressed through restoring adjacent contacts, adjusting occlusion, reshaping teeth or prostheses, and modifying both adjacent and opposing teeth. Horizontal impaction is managed with periodontal therapy, gingival and papillary reconstruction, addressing dentition deficiencies, and promoting oral hygiene and healthy lifestyle habits. It is crucial to avoid iatrogenic factors as well. Despite advancements in classification and treatment approaches, several limitations persist, including insufficient personalized treatment planning, a lack of longitudinal studies, and inconsistent multidisciplinary collaboration. Future research should prioritize the development of personalized treatment strategies, long-term studies, and the application of innovative technologies to improve treatment outcomes and reduce the incidence of food impaction.